Options clinical manifestations of giardiasis in children - Abdukadirova N.B; Xayatova Shoira Telmanovna (Genius Journals, 2023)
In our study of patients identified the following options for the clinical manifestations of giardiasis contact allocated latent, subclinical and clinical form of giardiasis. We divided the latent, subclinical, and clinical forms of lyamliosis. In the latent form, the children did not complain, and the separation of the cysts averaged 0.6 cysts at the construction site. In subclinical and clinical forms, pain in the abdominal area, intestinal and gastric dyspepsia syndrome was observed. Separation of cysts in the subclinical form revealed 1.5 cysts at the construction site. In the clinical form of giardiasis, the clinical picture was bright, with the separation of cysts, on average, 2.5 cysts were found in the drying area. Dietary and drug therapy against lyamliosis is prescribed, distinguishing between latent, subclinical and clinical forms
Keywords: Children; giardiasis; clinical types